Drug-induced herpes zoster: a pharmacovigilance analysis of FDA adverse event reports from 2004 to 2024 - Xia, Jiali; Zhang, Jing; Zhu, Hongyu; Ding, Li (Frontiers in Pharmacology, 2025)
BackgroundHerpes zoster severely impacts patients’ quality of life and therapeutic results. This research utilized data from the FDA Adverse Event Reporting System (FAERS) to examine the prevalence and attributes of drug-induced herpes zoster.MethodsWe analyzed FAERS reports about zoster from Q1 2004 to Q3 2024 and developed a list of possible pathogenic agents. Ranked the 30 medicines with the greatest incidence of reported herpes zoster cases. Statistical disproportionality analysis was employed to identify an elevated reporting frequency of herpes zoster linked to a particular medication.ResultsHerpes zoster was referenced in 50,164 FAERS reports from 2004 to 2024. The majority of the implicated drugs were immunosuppressants. Anifrolumab exhibited the greatest ROR and PRR ratings among the drugs evaluated. Furthermore, rozanolixizumab, tozinameran, elapegademase, and other medications not indicated for inducing herpes zoster were recognized, underscoring the necessity for increased clinical vigilance and awareness. Nonetheless, these correlations should be regarded with caution, as they do not establish a direct causative relationship.ConclusionThis study underscores the need of pharmacovigilance in recognizing and comprehending drug-induced herpes zoster. Additional research is required to validate these findings and to design strategies for risk management and reduction to enhance treatment outcomes in patients.